Gynecologic Oncology: On the Shoulders of Giants - Kulkarni, Rohini; Gupta, Sudeep; Maheshwari, Amita (Indian Journal of Medical and Paediatric Oncology, 2022)
Gynecologic oncology is considered a new field, but its roots are buried deep in the past. As with other tumors, the earliest progress in modern times started with anesthesia and surgery. This was followed by landmark achievements in pathology, cytology, radiotherapy, chemotherapy, tumor virology, generation of high-quality evidence, and, more recently, genetics and genomics. Some of the most notable progresses in gynecologic cancers have been made by integrating the expertise of various specialties in multimodality management approaches. In this article we review the most important milestones in the history of gynecologic oncology and acknowledge the contributions of pioneers who made these possible.
Keywords: gynecologic oncology; history; treatment